A child's book of art : great pictures, first words - Micklethwait, Lucy. (New York : Dorling Kindersley, 1993)
An introduction to art that uses well-known works of art to illustrate familiar words and concepts.
The family -- Wild animals -- Counting -- Opposites -- Faces -- A time to play -- A time for peace.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
1.7.
1.7
K-3
Keywords: Art appreciation -- Juvenile literature; Art appreciation; Vocabulary; Art appreciation; Vocabulary